2023
DOI: 10.53955/jsderi.v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Petroleum and Natural Gas on the Sustainable Development of Indonesian Economy

Abstract: Throughout the history of national development, petroleum and natural gas have played a vital and strategic role, serving as essential energy sources for various economic activities. The petroleum and gas sector also contributes significantly to state revenue through the management of these resources. The author aims to discuss the appropriate utilization of petroleum and natural gas and its potential to enhance economic income in Indonesia. Petroleum and natural gas, as valuable resources, exist in liquid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…[10] If this relates to the definition of corporate crime provided previously, it can be concluded that further research on the urgency of corporate criminal responsibility is required to realize the effectiveness of environmental criminal law enforcement. [11] In addition, it is necessary to analyze the appropriate criminal justice system to be applied to corporate criminal acts in the environmental field in order to create economic justice (the economic conception of justice), according to which the law can create efficiency that regulates and creates justice. [12] 4th INCLAR…”
Section: Introductionmentioning
confidence: 99%
“…[10] If this relates to the definition of corporate crime provided previously, it can be concluded that further research on the urgency of corporate criminal responsibility is required to realize the effectiveness of environmental criminal law enforcement. [11] In addition, it is necessary to analyze the appropriate criminal justice system to be applied to corporate criminal acts in the environmental field in order to create economic justice (the economic conception of justice), according to which the law can create efficiency that regulates and creates justice. [12] 4th INCLAR…”
Section: Introductionmentioning
confidence: 99%